STRATEGI PENGENDALIAN MANAJAMEN DALAM RANGKA EFISIENSI BIAYA PRODUKSI PADA PT. BHIMEX SAMARINDA - Venska Marsela Putri Diva Tani (JURNAL ILMIAH RESEARCH STUDENT, 2023)
This research aims to determine the implementation of management control strategies in cost-efficient production and analyze production cost control using the standard cost method at PT. Bhimex Samarinda. Standard cost is the planned cost before the production process takes place, and the actual cost is known after the production process is completed. This research is descriptive with a qualitative approach, using primary and secondary data sources. Data collection techniques used include observation, interviews, and documentation. From the analysis results, it can be concluded that the implementation of management control strategies carried by PT. Bhimex Samarinda aligns with the elements of management control. Based on the analysis of variances conducted by the researcher in comparing standard production costs and actual costs that occurred at PT. Bhimex Samarinda in the quarterly period of January, February, and March 2023. In January, it amounted to Rp 418,200, indicating a favorable result. Meanwhile, in February, an unfavorable variance analysis, amounting to Rp -409,000. In March, a variance analysis of Rp 686,400 which means it is favorable.